FABRIKASI DAN KARAKTERISASI MEMBRAN STYROFOAM DENGAN METODE ELEKTROSPINNING UNTUK PEMISAHAN MINYAK/AIR - Fitria Basuki Sukandaru; Rena Juwita Sari; Maria Ratih Puspita; Akhmad Kusumaatmaja (KURVATEK, 2021)
Membrane separation technology is a new technology in oily wastewater treatment. High efficiency and relatively smooth operational processes are the main advantages that need to be looked at in membrane separation. Characterization of the styrofoam nanofiber membrane as an oil/water filter has been completed. Styrofoam membrane is made by electrospinning method with solvent concentration of 5 ml, 10 ml, 15 ml and 20 ml. In addition, the membrane filtration process test equipment was also made. The results of the FTIR spectrum of membrane filtration results explained that the new absorption peak of 1442.80 cm-1 caused an increase in membrane hydrophilic, at the absorption peak of 2841 cm-1 and an increase in absorption peak of 2926.13 cm-1 occurred due to the presence of water content in the membrane after testing. Whereas the absorption peak of 2084.49 cm-1 indicates an interaction between compounds in orange peel (phenolic, flavonoid and triterpenoid) with oil. Meanwhile, SEM results of styrofoam membranes after filtration showed that the size of the nanofiber became larger (swelling) and fouling occurred around the pore causing narrowing of the pore. This causes a decrease in permeability but increased selectivity. Keywords: membrane, styrofoam, nanofiber, electrospinning, oil water filtration